The yeast protein Arc1p binds to tRNA and functions as a cofactor for the methionyl‐ and glutamyl‐tRNA synthetases. - Simos, Geōrgios; Segref, Alexandra; Fasiolo, Franco; Hellmuth, Klaus; Shevchenko, Andrei; Mann, Mattias; Hurt, Ed (The EMBO journal, 1996)
Arc1p was found in a screen for components that interact genetically with Los1p, a nuclear pore‐associated yeast protein involved in tRNA biogenesis. Arc1p is associated with two proteins which were identified as methionyl‐tRNA and glutamyl‐tRNA synthetase (MetRS and GluRS) by a new mass spectrometry method. ARC1 gene disruption leads to slow growth and reduced MetRS activity, and synthetically lethal arc1‐ mutants are complemented by the genes for MetRS and GluRS. Recombinant Arc1p binds in vitro to purified monomeric yeast MetRS, but not to an N‐terminal truncated form, and strongly increases its apparent affinity for tRNAMet. Furthermore, Arc1p, which is allelic to the quadruplex nucleic acid binding protein G4p1, exhibits specific binding to tRNA as determined by gel retardation and UV‐cross‐linking. Arc1p is, therefore, a yeast protein with dual specificity: it associates with tRNA and aminoacyl‐tRNA synthetases. This functional interaction may be required for efficient aminoacylation in vivo.
Gesehen am 29.01.2026